1978
DOI: 10.1159/000122833
|View full text |Cite
|
Sign up to set email alerts
|

<i>In vitro </i>Release of ACTH from Dispersed Rat Pars intermedia Cells. III. Multiple Forms of ACTH Biological Activity

Abstract: We have reported that both an extract of rat hypothalamus-stalk-median eminence (HE) and 5-hydroxytryptamine (5-HT) will stimulate the release of ACTH biological activity from acutely, non-enzymically dispersed rat pars intermedia (PI) cells. We have also found that the ACTH activity within the PI cells is composed of 4 chromatographically separable entities, but only a small proportion of the total ACTH activity co-elutes with ACTH1-39. In the present study we subjected the media, after incubation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

1980
1980
1988
1988

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 8 publications
3
8
0
Order By: Relevance
“…We previously reported that larger fragments of POMC also have some ACTH bioactivity [13]. We confirm the findings of Scott et al (24), that CLIP has no corticotropic activity.…”
Section: Characterisation Of the Assayssupporting
confidence: 92%
See 2 more Smart Citations
“…We previously reported that larger fragments of POMC also have some ACTH bioactivity [13]. We confirm the findings of Scott et al (24), that CLIP has no corticotropic activity.…”
Section: Characterisation Of the Assayssupporting
confidence: 92%
“…2). The release of ACTH bioactivity increased in response to the serotonin in a dose-related manner in agreement with previous findings [8,13,15]. During the high dose of seroto nin, it reached a level 2.5-fold higher than control within 3 min.…”
Section: Effect Of Serotonin On the Release O F Pi Peptidessupporting
confidence: 92%
See 1 more Smart Citation
“…as suggested by the com pletely different changes noted in the concentration of bio active ACTH. Corticotropic activity of PI from adult mice and rats [8,16,37] is due to peptides of high, medium and low molecular weights; various entities containing the NH:-terminal portion of 1-39 ACTH have also been demonstrat ed in rat NIL by using R1A [8,13,17,21,24]; the relative proportion of the peptides varying according to the authors. Both high (30k) and medium (20k) molecular weight pep tides have been shown to serve as precursors in the process of biosynthesis of a-MSH and other peptides [5,18]; there is a controversy with regard to occurrence and concentration of low molecular weight ACTH [13].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Kraicer et al [14] have shown that the ACTH biological activity re leased by stimulated 1L cells was due to 4 classes of pep tides which could be separated by gel chromatography, and only a small proportion (10%) of the total ACTH activity coeluted with ACTH1'39. Thus, we might question the chemical nature of the products which are released in our conditions.…”
Section: Discussionmentioning
confidence: 99%